2017
DOI: 10.1111/desc.12539
|View full text |Cite
|
Sign up to set email alerts
|

Young children perceive less humanness in outgroup faces

Abstract: Article:McLoughlin, Niamh Caitriona, Tipper, Steven Paul orcid.org/0000-0002-7066-1117 and Over, Harriet orcid.org/0000-0001-9461-043X (2017) Young children perceive less humanness in outgroup faces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 69 publications
2
48
0
1
Order By: Relevance
“…Dispositional levels of anthropomorphism and dehumanization work in concert with knowledge and stimulus cues. Similarly, not only are developmental considerations important to further our understanding of the behavioral and brain mechanisms supporting the attribution of socialness, they are crucial given that both children and the elderly are target groups for the deployment of social robots, and age‐dependent effects have been reported with regard to socialness attribution . Finally, group and cultural differences that determine the scope of attribution of socialness are likely at play.…”
Section: Discussionmentioning
confidence: 99%
“…Dispositional levels of anthropomorphism and dehumanization work in concert with knowledge and stimulus cues. Similarly, not only are developmental considerations important to further our understanding of the behavioral and brain mechanisms supporting the attribution of socialness, they are crucial given that both children and the elderly are target groups for the deployment of social robots, and age‐dependent effects have been reported with regard to socialness attribution . Finally, group and cultural differences that determine the scope of attribution of socialness are likely at play.…”
Section: Discussionmentioning
confidence: 99%
“…McLoughlin and Over () found that 5‐ and 6‐year‐olds used more mental state words (e.g., knowing, deciding, pretending, tricking) to describe characters they believed were from their in‐group (same‐gender or from the same geographical region) compared to out‐group members. In another study, McLoughlin, Tipper, and Over () found that children perceived less humanness in out‐group members compared to in‐group members. Prejudice toward dissimilar out‐groups was not directly measured in these studies, yet some form of in‐group favoritism (i.e., prejudice) might also be related to children's mentalizing (Brown, ; McLoughlin & Over, ).…”
Section: Mindreading For In‐group Vs Out‐groupmentioning
confidence: 98%
“…Because our sample consisted of Turkish children, the target in‐group was Turkish. This allowed us to examine whether previous studies’ findings regarding mindreading in out‐group members (e.g., McLoughlin et al., ) would extend beyond children in Western, educated, industrialized, rich, and democratic (WEIRD) cultures. In addition, whereas past research examined a single out‐group, this study used two out‐groups (Syrians and Northern Europeans), allowing us to compare similarity, threat and prejudice as contributors to mindreading.…”
Section: Mindreading For In‐group Vs Out‐groupmentioning
confidence: 99%
“…For example, by the age of five, children prefer members of their own gender, language and racial group on both explicit and implicit measures (Aboud, ; Dunham, Baron, & Banaji, ; Kinzler, Dupoux, & Spelke, ). Young children growing up in a number of different cultural contexts are also observed to report greater liking for national and ethnic ingroup members compared to individuals whose national or ethnic identity is different to their own (Bar‐Tal, ; Bennett, Barrett, Karakozov, Kipiani, Lyons, Pavlenko, & Riazanova, ; Cameron, Rutland, Brown, & Douch, ; McLoughlin, Tipper, & Over, ). These social group preferences extend to how prosocial children are towards other people.…”
Section: Introductionmentioning
confidence: 99%